KEEFEKTIFAN MEDIA SIMULASI UNTUK MENINGKATKAN PEMAHAMAN KONSEP DAN KETERLIBATAN BELAJAR SISWA (UPEJ Unnes Physics Education Journal, 2013)
The ambiguity and complexity of the material presented teacher to the student is one of the causes of less than optimal student learning outcomes. Media simulations are meant to attract the attention of students and facilitate understanding of the concept of light reflection. The purpose of this research is to increase understanding of the concept of student learning and engagement. The research method used a control group pretest posttes design. The data are collected Â by using documentation, observation, and tests metods. Analysis of the test data using the formula to determine the gain of improving student learning outcomes and t-test to test the hypothesis. Based on the test results obtained cognitive learning gains in classroom experiments <g> faktor of 0.62 and a control class <g> of 0,55. Large <g> Â factor at 0.80 for the presence of affective aspects, attention 0.52, 0.13 responsibility, expression 0.45, 0.48 and group cooperation. the result t-test the left side with two samples obtained t_hitung of 0.362, while t_tabel at 5% significance level with 62 df is 1.670 so thitung>-ttabel which shows that the learning outcomes using teaching materials with simulated media is better or equal to the results learn to use the textbooks. It can be concluded that using instructional materials with simulated media can increase learning outcomes and student engagement.